P202 A survey of ILD expertise availability and High Resolution Computer Tomography (HRCT) protocols used in patients with Interstitial lung disease (ILD) across hospitals in England. (14th November 2013) - Balata, H; Ashish, A; Aziz, I
Abstract : Introduction and aims: ILD is increasingly being recognised as complex condition necessitating a multi-disciplinary approach to diagnosis and management requiring availability of a clinician and a radiologist with declared interest in ILD. HRCT is the imaging of choice used for assessment of ILD. The BTS ILD guidelines do recommend a "standard" HRCT protocol to be used in diagnosis of patients with ILD. It is however not known if there is a uniform availability of expertise within different centres in England and if "standard "HRCT protocol as recommended is being followed. Method: A questionnaire was handed to radiologists with special interest in thoracic imaging working in different hospitals sites in England, at an ILD radiology conference. Questionnaires enquired about availability of ILD services and HRCT scanning technique used at their establishment. Results: Of the 150 questionnaires, 100 were returned for analysis. There were responses from 39 teaching hospitals and 61 district general hospitals (DGH). Abstract P202 Table 1. Results of questionnaire given to thoracic radiologists across Hospitals in England. Conclusions: Despite increasing focus on ILD as a sub-speciality, there is still a significant difference in the provision of expert care within district general hospitals in UK for patients with ILD. This may affect the quality of care provided with potential to variability of care standards. The "standard protocol" for HRCT techniques as specified by BTS is not being followed in England. Despite recommendations from BTS, aspects of HRCT scanning technique applied were variable and influenced by local preferences and expertise. This may lead to differences in scan interpretation, diagnosis and outcomes. This gap in provision of care and variability of techniques should be bridged to ensure uniformity of care and outcomes. References: NICE guidelines, June 2013; CG163 2: Thorax ; 63 (Suppl V); v1-v58